Inhibitory effect of Probiotics on some Gram positive and negative Bacteria - Aamer Alchalaby; Semaa AL-Abedi (Basrah Journal of Veterinary Research)
The present study's objective was to evaluate the inhibitory activity of the Probiotics Lactobacillus acidophilus and Bifidobacterium (obtained from the Agriculture Research Directorate, Ministry of Science and Technology, Iraq) and a suspension of a mixture between the two mentioned probiotics with two types of Gram-negative bacteria (Pseudomonas spp and Proteus spp) and one type of Gram-positive bacteria (Streptococcus spp) in vitro. The required tests were completed to verify the probiotics' purity, and the bacterial isolates used in the current investigation were assessed using biochemical assays and selected culture medium (culture and microscopic features). In addition, the inhibitory efficacy of the investigated Probiotics in different Gram positive and negative bacteria was evaluated by drug susceptibility testing (disc diffusion test as well as agar well diffusion test). Our data of the current study confirmed an excellent inhibitory activity of each Bifidobacterium (B) and the mixture of the two probiotics (MLB) via measuring the inhibition area, they had 25, 22mm, 28,-30 mm inhibition zone for Pseudomonas spp, 23, 25 mm, 26-27mm inhibition zone for Proteus species spp, and 22,20 mm, 33,29 mm inhibition quarter for Streptococcus species, by way of the usage of disc and agar well diffusion methods respectively. Where it was once weak inhibition activity of Lactobacillus acidophilus (L)on Pseudomonas spp, 0-3 mm and Streptococcus species 1-7 mm by the usage ofthe disc and agar well diffusion respectively. On the other, hand, Probiotic(Lactobacillus acidophilus) had available zone of inhibition on the Proteus sppbacteria, which were 24, 24 mm through the disc and agar well diffusion respectively. In conclusion: the Probiotics were found to have good and active inhibitory action on Gram-positive microorganism (Streptococcus) and gram-negative microorganism (Pseudomonas and Proteus) in vitro by way of using disc and agar well diffusion test, and the combination of the two probiotics MBL of present study, had more potent inhibitory action than each one of the studied separate probiotics.